Christmas mittens murder - Hollis, Lee; Cahoon, Lynn; Day, Maddie (Hollis, Lee. Hayley Powell food and cocktails mystery, 2023)
Three Christmas themed novellas feature Hayley Powell, Mia Malone, and Cece Barton all trying to solve suspicious deaths in unexpected circumstances.